Enhanced thermoelectric performance of SnTe alloy with Ce and Li co-doping. (December 2019) - Guo, F.; Cui, B.; Guo, M.; Wang, J.; Cao, J.; Cai, W.; Sui, J.
Abstract: SnTe alloy is a kind of potential medium-temperature thermoelectric material to replace toxic PbTe. In this work, we demonstrate that both trivalent Ce doping and univalent Li doping can optimize the thermoelectric properties of SnTe by controlling carrier concentration in two directions, respectively. In addition, the dispersed high-density nano-precipitates caused by Li doping are helpful to enhance the phonon scattering and then reduce the lattice thermal conductivity. Moreover, co-doping of Ce and Li promotes the peak ZT and average ZT of SnTe simultaneously. The ZT value reaches approximately1 at 873 K and the ZT ave reaches approximately 0.39 from 300 K to 873 K for Sn0.98 Ce0.02 Te-(Li2 Te)0.01 . Graphical abstract: Image 1 Highlights: Both increasing and decreasing carrier concentration can improve the thermoelectric properties of pure SnTe. Dense and dispersive nano-precipitates are introduced. ZT value and average ZT value are improved by cerium and lithium co-doping.